ANÁLISE FRACTAL E MULTIFRACTAL DA RESISTÊNCIA DO SOLO À PENETRAÇÃO. - RODRIGUEZ LEIVA, Jairo Osvaldo (2018)
The productivity of the crops is negatively affected by the resistance of the soil to the penetration (PR), which can interfere in the development of roots and present high horizontal and vertical variability. Thus, the objective of this research was to evaluate PR through fractal and multifractal techniques in vertical profiles. The data were obtained in two experimental areas, one cultivated with sugarcane and the other with soybean. In both areas, 60 sampling points (sugarcane) and 70 (soybean) are marked with the help of a GPS with differential correction. The area with sugarcane (Saccharum officinarum L.) is 6.85 ha and is located in the municipality of Coelho Neto (MA) with irrigation by linear pivot in the dry period. The area under soybean (Glycine max L.) cultivated under no-tillage has 44.75 ha and is located in the municipality of Mata Roma (MA). The PR, in the 0.0-0.6 layer each of the sampling points, was determined by means of a Planalsucar-Stolf impact penetrometer, the same PR being determined every 0.01 m to allow statistical analysis and multifractal data . The PR charts were constructed in depth for each of the profiles. Aiming to enable the statistical and multifractal analysis of the data. In the cultures studied, multifractal analysis allowed the identification of patterns at different scales and with high heterogeneity. The multifractal behavior was represented by the singularity spectrum (α) versus f (α), and by the generalized dimension (Dq). The multifractal analysis allowed the differentiation between the profiles of the relief units (Type A, B, C and D) in the The use of multifractal techniques in the soybean crop for the study of PR in the 70 sampling points and in the Type A and Type B pedoforms allowed the identification of heterogeneity of the RPminimum data that are not detected by The study of PR in the different pedoforms allowed us to describe greater heterogeneity of scale for the shape of concave relief, demonstrating that the fractal analysis was efficient to ascertain the differences in PR throughout the landscape for the vertical profiles.